“Bildtapeten” and the conservation of medieval wall paintings at the turn of the twentieth century in Germany - Ursula Schädler-Saub (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In the last decades of the nineteenth Century, a paradigm change in the preservation of medieval wall painting conservation took place. Restoration as equivalent of repainting was definitely refused. The goal of all efforts was now to preserve the uncovered wall paintings in their authentic state. However, the presentation of fragmentary wall paintings in churches required compromises between historical values and liturgical needs. German examples with so called “Bildtapeten” (picture wallpapers) illustrate such a clever compromise: roller blinds with fully integrated versions of the scenes depicted in full size on paper, were mounted on the walls over the fragmentary wall paintings; they could be raised for the experts and lowered for the general public. Alois Riegl in his important essay of 1903, “Questions on the restoration of wall paintings”, criticised this method and emphasized the complexity of meeting the demands of modern wall painting conservation.